I am following the Functional Programming in Scala lecture on Coursera and at the end of the video 5.7, Martin Odersky asks to prove by induction the correctness of the following equation :
(xs ++ ys) map f = (xs map f) ++ (ys map f)
How to handle proof by induction when there are multiple lists involved ?
I have checked the base cases of xs being Nil and ys being Nil. I have proven by induction that the equation holds when xs is replaced by x::xs, but do we also need to check the equation with ys replaced by y::ys ?
And in that case (without spoiling the exercise too much...which is not graded anyway) how do you handle : (xs ++ (y::ys)) map f
?
This is the approach I have used on a similar example, to prove that
(xs ++ ys).reverse = ys.reverse ++ xs.reverse
Proof (omitting the base case, and easy x::xs case) :
(xs ++ (y::ys)).reverse
= (xs ++ (List(y) ++ ys)).reverse //y::ys = List(y) ++ ys
= ((xs ++ List(y)) ++ ys).reverse //concat associativity
= ys.reverse ++ (xs ++ List(y)).reverse //by induction hypothesis (proven with x::xs)
= ys.reverse ++ List(y).reverse ++ xs.reverse //by induction hypothesis
= ys.reverse ++ (y::Nil).reverse ++ xs.reverse //List(y) = y :: Nil
= ys.reverse ++ Nil.reverse ++ List(y) ++ xs.reverse //reverse definition
= (ys.reverse ++ List(y)) ++ xs.reverse //reverse on Nil (base case)
= (y :: ys).reverse ++ xs.reverse //reverse definition
Is this right ?
The property involves multiple lists, but ++
only recurses on its left argument. That's a hint that you can prove by induction on that left argument. In general, when proving a proposition about some recursive function, the first thing you try is inducting on the same argument that function recurses on.
I'll do this one for you as an example:
Claim: (xs ++ ys) map f
= (xs map f) ++ (ys map f)
Proof: by induction on xs
.
Base case: xs
= Nil
lhs = (Nil ++ ys) map f
= ys map f
(by ++
's definition)
rhs = (Nil map f) ++ (ys map f)
= Nil ++ ys map f
= ys map f
(by map
's, then ++
's definitions)
Inductive case: xs
= z :: zs
(zs ++ ys) map f
= (zs map f) ++ (ys map f)
((z :: zs) ++ ys) map f
= ((z :: zs) map f) ++ (ys map f)
lhs = (z :: (zs ++ ys)) map f
= f(z) :: ((zs ++ ys) map f)
(1)
(by map
's definition)
rhs = ((z :: zs) map f) ++ (ys map f)
= (f(z) :: (zs map f)) ++ (ys map f)
(by map
's definition)
in turn, rhs = f(z) :: ((zs map f) ++ (ys map f))
(2)
(by ++
's definition)
Therefore, we have proven the claim to be true reguardless of xs
, ys
, and f
.